2013
DOI: 10.1007/s13277-013-1442-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the expression of cyclin G2 in esophageal cancer cell and its significance

Abstract: This study aimed to analyze the expression, clinical significance of cyclin G2 (CCNG2) in esophageal carcinoma, and the biological effect in its cell line by CCNG2 overexpression. Immunohistochemistry and western blot were used to analyze CCNG2 protein expression in 73 cases of esophageal cancer and normal tissues to study the relationship between CCNG2 expression and clinical factors. CCNG2 lentiviral vector and empty vector were respectively transfected into esophageal cancer Eca-109 cell line. Reverse trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Previous studies have reported that CCNG2 participates in carcinogenesis and is a known tumor suppressor gene (15)(16)(17)(20)(21)(22)(23)(24)(25)(26). CCNG2 gene expression is downregulated in thyroid (20), oral (21), ovarian (22), breast (23,24), gastric (16), esophageal (17), prostate (25), kidney (26) and colorectal (15) cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported that CCNG2 participates in carcinogenesis and is a known tumor suppressor gene (15)(16)(17)(20)(21)(22)(23)(24)(25)(26). CCNG2 gene expression is downregulated in thyroid (20), oral (21), ovarian (22), breast (23,24), gastric (16), esophageal (17), prostate (25), kidney (26) and colorectal (15) cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our previous study demonstrated that CCNG2 was associated with chemoresistance and cancer stemness via cell apoptosis in pancreatic cancer (13). Recently, CCNG2 has been reported as a novel prognostic marker in several types of cancer (14)(15)(16)(17). However, to date, no study has clarified the association between CCNG2 and the prognosis of pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous data showed that as a key negative regulator of cell cycle proliferation, apoptosis, cell death signaling, and even carcinogenesis, suggesting that the decreased expression levels of CCNG2 significantly correlates with tumor progression and unfavorable prognosis, such as studies in colorectal carcinoma, kidney, esophageal, oral cancer, gastric carcinoma, prostate cancer and papillary carcinoma of the thyroid (29)(30)(31)(32)(33)(34)(35). In the present study, we found that CCNG2 expression was markedly decreased in the LSCC tissues compared with the adjacent normal tissues and lower expression of CCNG2 tended to have more advanced clinical stage.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of CycG2 is repressed by mitogens, however, is upregulated during cell cycle arrest responses to antiproliferative signals (16). The expression of CycG2 decreased in thyroid cancer, esophageal, prostate, kidney and gastric cancer tissues and cells, and is significantly correlated with lymph node metastasis, clinical stage, histological grade and poor overall survival, suggesting that CCNG2 may be important as a negative regulator in thyroid cancer K1 cells by promoting the degradation of CDK2 (17)(18)(19)(20)(21). In addition, abnormal expression of CycG2 was observed in nasopharyngeal carcinoma cells and was closely associated with tumor differentiation, origin and progression (22).…”
Section: Introductionmentioning
confidence: 99%